Diwali : Celebrations in my worlds - Torpie, Kate (New York : Crabtree Publishing, 2009)
The 'festival of lights' is one of the most popular festivals in the Hindu calendar. Like most Hindu festivals, Diwali celebrates the triumph of good over evil. According to one legend Diwali is observed to mark the return of Lord Rama to his homeland.
Keywords: Multicultural -- Picture -- Non-fiction